A avaliação nacional da alfabetização e a prática docente no bloco inicial de alfabetização: estudo de caso na rede pública do Distrito Federal - Souza, Thamara Maria de (2019)
The object of this research is the National Literacy Assessment (ANA). ANA was created and instituted by the Ministry of Education (MEC) to monitor the effectiveness of the National Pact for Literacy in the Right Age (PNAIC). It aims to measure the level of literacy and literacy in Portuguese and Mathematics of students enrol led in the 3rd year of the Initial Block of Literacy (BIA) of the public school system of the country. This research is linked to the Policy Research, Management and Education Evaluation Line of the Stricto Sensu Postgraduate course, Master in Education, of the Catholic University of Brasilia (UCB). The general objective of this research is to analyze how the National Literacy Assessment (ANA) is perceived by the teachers of the Initial Block of Literacy (BIA) in a public school in the Federal District (DF). For that, the following specific objectives were defined: 1) to characterize the historical trajectory of Literacy in Brazil and the implantation of the school organization in cycles in the DF; 2) describe the ANA production context and the alignment of the BIA with this policy; 3) to examine convergences and divergences between the practice of the sample (case study) and what is recommended in the ANA guidelines. For this empirical research, a case study was carried out of a school class of Núcleo Bandeirante, of the public school system, which obtained the best Index of Development of Basic Education (Ideb) among the schools belonging to the Regional Coordination of Teaching of Núcleo Bandeirante (CRENB). With the current situation, revealed by the Demographic Census of 2016, of the high rate of non-approval, of the students of the 3rd year of elementary school, of the public school system of the country, it is very important to discuss together with the teachers the policy that evaluates the offer conditions of the education of children up to eight years of age. This research becomes relevant because it offers information to understand the ANA as a public policy of induction to improve the quality of literacy. For the study, a basic, exploratory research with a qualitative approach was carried out. To compose the research, data were collected through a questionnaire with the BIA teachers and interview with a member of the management team. Considering the ANA's objective of inserting itself in the BIA in order to evaluate the redirection of the teaching-learning process in the classroom and also to induce the production of educational policies aimed at improving the quality of literacy in the country, the results of the research indicate that, in the perception of teachers working in literacy classes, there is a gap between the objective that ANA proposes and its actual practice.